Identification of bacterial species in milk by MALDI-TOF and assessment of some oxidant-antioxidant parameters in blood and milk from cows with different health status of the udder - Ozbey, G.; Cambay, Z.; Yilmaz, S.; Aytekin, O.; Zigo, F.; Ozcelik, M.; Otlu, B. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2022)
This study aimed to identify bacterial pathogens in milk samples from dairy cows with sub -clinical and clinical mastitis as well as to assess the concentrations of oxidant-antioxidant param-eters [malondialdehyde (MDA), reduced glutathione (GSH), and total GSH levels] in both blood and milk samples. From a total of 200 dairy cows in 8 farms, 800 quarter milk samples obtained from each udder were tested in the laboratory for the presence of udder pathogens. Cultivated bacteria causing intramammary infection from milk samples were identified by Matrix-Assisted Laser Desorption/Ionization-Time of Flight (MALDI-TOF). In addition, from tested animals 60 cows were selected includ??ng 20 healthy cows that were CMT negative, 20 cows with subclini-cal mastitis (SM), and 20 cows with clinical mastitis (CM) for detection of MDA, GSH, and total GSH levels in blood and milk samples. Three hundred and eighty (47.5%; 380/800), 300 (37.5%; 300/800), and 120 (15%; 120/800) of milk samples, respectively were CMT positive or SM and CM, and those positives were cows from different farms. We observed that 87.4% (332/380), 25.3% (76/300), and 34.2% (41/120) of cows with CMT positive, CMT negative, and CM had bacterial growth. The most predominantly identified bacteria were Staphylococcus chromogenes (18.7%) obtained mainly from SM and Staphylococcus aureus (16.7%) as the most frequent cau-se of CM. According to our results, dairy cows with CM had the highest MDA levels, the lowest GSH, and total GSH levels in both blood and milk samples however, high MDA levels and low GSH levels in milk samples with SM were observed. Based on our results, lipid oxidant MDA and antioxidant GSH could be excellent biomarkers of cow???s milk for developing inflammation of the mammary gland. In addition, there was no link between nutrition and MDA and GSH levels.
Keywords: dairy cows; CMT; mastitis; malondialdehyde; glutathione; MALDI-TOF